Diffuse large B‐cell lymphoma with primary treatment failure: Ultra‐high risk features and benchmarking for experimental therapies. Issue 2 (February 2017) - Costa, Luciano J.; Maddocks, Kami; Epperla, Narendranath; Reddy, Nishitha M.; Karmali, Reem; Umyarova, Elvira; Bachanova, Veronika; Costa, Cristiana; Glenn, Martha J.; Chavez, Julio C.; Calzada, Oscar; Lansigan, Frederick; et al.
Abstract: The outcomes of patients with DLBCL and primary treatment failure (PTF) in the rituximab era are unclear. We analyzed 331 patients with PTF, defined as primary progression while on upfront chemoimmunotherapy (PP), residual disease at the end of upfront therapy (RD) or relapse < 6 months from end of therapy (early relapse; ER). Median age was 58 years and response to salvage was 41.7%. Two‐year OS was 18.5% in PP, 30.6% in RD and 45.5% in ER. The presence of PP, intermediate‐high/high NCCN‐IPI at time of PTF or MYC translocation predicted 2‐year OS of 13.6% constituting ultra‐high risk (UHR) features. Among the 132 patients who underwent autologous hematopoietic cell transplantation, 2‐year OS was 74.3%, 59.6% and 10.7% for patients with 0, 1 and 2–3 UHR features respectively. Patients with PTF and UHR features should be prioritized for clinical trials with newer agents and innovative cellular therapy.